Conjectura de Artin: um estudo sobre pares de formas aditivas - Camacho, Adriana Marcela Fonce (2014)
This work is based mainly on the Brunder and Godinho article [2] which shows proof of the conjecture of Artin methods using p-adic, although the conjecture is stated on the real numbers which makes the proof is show an equivalence on the field of the number p-adic method with the help of colored variables ya contraction of variables so as to prove the statement, taking the first level and ensuring a nontrivial solution in the following levels.